Celebrating the 1st Asia laboratory animal day: a commitment to ethical research and animal welfare / John Shia Kwong Siew - Shia, John Kwong Siew (Faculty of Pharmacy, 2024)
On September 12, 2024, Professor Dr. Chin Quan, President of the Asian Federation of Laboratory Animal Science (AFLAS), announced that every November 29th would be Asia Laboratory Animal Day (ALAD), a celebration honouring the contributions of laboratory animals to scientific discoveries. The first-ever ALAD celebration in Malaysia was held on November 27, 2024, at the Laboratory Animal Facility and Management (LAFAM), Faculty of Pharmacy UiTM, in partnership with the Laboratory Animal Science Association of Malaysia (LASAM).